2017
DOI: 10.1007/82_2017_53
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Vaccine Development During the 2013–2016 West African Ebola Virus Disease Outbreak

Abstract: The Ebola virus disease outbreak that began in Western Africa in December 2013 was unprecedented in both scope and spread, and the global response was slower and less coherent than was optimal given the scale and pace of the epidemic. Past experience with limited localized outbreaks, lack of licensed medical countermeasures, reluctance by first responders to direct scarce resources to clinical research, community resistance to outside interventions, and lack of local infrastructure were among the factors delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Pharmacists are a critical part of healthcare systems, carrying out gorgeous title roles in the untimely pandemics and health crises, with some like Ebola and Zika creating world health collateral perils also. Likewise, by using pitching-in in the avoidance, alertness, discovery, and feedback to COVID-19 pandemic pharmacists and pharmaceutical scientists are conveying their responsibility towards public fitness in consideration of this disaster [35][36][37] . In various countries, pharmacies have worked in immediate cooperation with the International humanitarian agencies like the Red Cross and native company employees to extend their reach to the public and to ensure domestic consignment of medicaments 38 -39 .…”
Section: Pharmacists and Pharmaceutical Scientistsmentioning
confidence: 99%
“…Pharmacists are a critical part of healthcare systems, carrying out gorgeous title roles in the untimely pandemics and health crises, with some like Ebola and Zika creating world health collateral perils also. Likewise, by using pitching-in in the avoidance, alertness, discovery, and feedback to COVID-19 pandemic pharmacists and pharmaceutical scientists are conveying their responsibility towards public fitness in consideration of this disaster [35][36][37] . In various countries, pharmacies have worked in immediate cooperation with the International humanitarian agencies like the Red Cross and native company employees to extend their reach to the public and to ensure domestic consignment of medicaments 38 -39 .…”
Section: Pharmacists and Pharmaceutical Scientistsmentioning
confidence: 99%
“…First identified in the 1970s, Ebola viruses are responsible for a frequently-fatal haemorrhagic fever disease. Their spread from Central to Western Africa led to a devastating outbreak between 2013 and 2016 [50]. Although initially delayed, the response strategy of the health community-integrated Phase I vaccination trials at an unprecedented pace.…”
Section: Yellow Fever Neisseria Meningitidis Cholera Ebola: How Vamentioning
confidence: 99%
“…This successful experience demonstrated how research can be accelerated in short delays when adequately supported/funded and appropriately championed. It also showed that clinical trials can be rapidly performed during outbreaks and could play a critical role in ending ongoing epidemics [50]. However, the use of rVSV-ZEBOV in response to a new epidemic that emerged in Democratic Republic of Congo at the end of 2017 and is not yet under control in September 2019 reminds us that even the most potent vaccines (> 97% estimated efficacy) must be administered timely to be effective [53].…”
Section: Yellow Fever Neisseria Meningitidis Cholera Ebola: How Vamentioning
confidence: 99%
“…EVD is caused by the highly pathogenic Ebola virus (EBOV), a member of the Filoviridae family [2]. The 2013-16 west-African Ebola virus epidemic was the largest outbreak ever recorded, with over 28,000 cases and 11,000 deaths, and exposed an urgent need for vaccination strategies to control future outbreaks [3,4]. The outbreak prompted the progression of a promising Vesicular Stomatitis Virus (VSV)vectored Ebola virus vaccine (designated V920, VSV-EBOV) through clinical trials [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%